2008
DOI: 10.1002/bit.22018
|View full text |Cite
|
Sign up to set email alerts
|

Effect of oxygen gradients on the activity and microbial community structure of a nitrifying, membrane‐aerated biofilm

Abstract: Shortcut nitrogen removal, that is, removal via formation and reduction of nitrite rather than nitrate, has been observed in membrane-aerated biofilms (MABs), but the extent, the controlling factors, and the kinetics of nitrite formation in MABs are poorly understood. We used a special MAB reactor to systematically study the effects of the dissolved oxygen (DO) concentration at the membrane surface, which is the biofilm base, on nitrification rates, extent of shortcut nitrification, and microbial community str… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

4
68
1

Year Published

2011
2011
2018
2018

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 116 publications
(75 citation statements)
references
References 58 publications
(94 reference statements)
4
68
1
Order By: Relevance
“…The lower half-saturation index of Nitrospira spp. for oxygen and nitrite as compared to other NOB groups has been observed in other studies at lab scale (Downing and Nerenberg, 2008;Blackburne et al, 2007). Similarly, organisms such as ammonium-oxidizing archaea or heterotrophic bacteria able to oxidize ammonia have been observed to be selected at low DO conditions in nitrifying systems (Kampschreur et al, 2007(Kampschreur et al, , 2009.…”
Section: Biology-limited Systemssupporting
confidence: 60%
“…The lower half-saturation index of Nitrospira spp. for oxygen and nitrite as compared to other NOB groups has been observed in other studies at lab scale (Downing and Nerenberg, 2008;Blackburne et al, 2007). Similarly, organisms such as ammonium-oxidizing archaea or heterotrophic bacteria able to oxidize ammonia have been observed to be selected at low DO conditions in nitrifying systems (Kampschreur et al, 2007(Kampschreur et al, , 2009.…”
Section: Biology-limited Systemssupporting
confidence: 60%
“…Many studies have reported the distribution transformation of Nitrobacter-like NOB and Nitrospira-like NOB (Gieseke et al, 2003;Downing and Nerenberg, 2008;Siripong and Rittmann, 2007;Terada et al, 2010), which were mainly carried out in activated sludge system, membrane aerated biofilm reactor or nitrification biofilters. The distribution of the NOB in CANON biofilter with high DO was still unclear.…”
Section: Distribution Of Nitrobacter-like Nob and Nitrospira-like Nobmentioning
confidence: 99%
“…Detachment not only occurred at granule surfaces, but on entire biofilm whorls starting from the core of granules. Such detachment can result in dual access of substrates by the surface and the core of granules, what is comparable to biofilms growing on porous membranes with substrate penetrating from both sides (Downing and Nerenberg, 2008), and should be considered in mass transport phenomena across granules. The FISH-CLSM micrographs suggested that the proliferation of Accumulibacter, Competibacter, and nitrifiers clusters occurred from granule core outwards.…”
Section: Figure 8 | Evolutions Of the Richness And Shannon's H' Divermentioning
confidence: 99%